2023
DOI: 10.21037/cdt-22-477
|View full text |Cite
|
Sign up to set email alerts
|

Aortic wall shear stress in bicuspid aortic valve disease—10-year follow-up

Abstract: Background: Bicuspid aortic valve (BAV) disease leads to deviant helical flow patterns especially in the mid-ascending aorta (AAo), potentially causing wall alterations such as aortic dilation and dissection. Among others, wall shear stress (WSS) could contribute to the prediction of long-term outcome of patients with BAV. 4D flow in cardiovascular magnetic resonance (CMR) has been established as a valid method for flow visualization and WSS estimation. The aim of this study is to reevaluate flow patterns and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Consistent follow-up holds immense importance in the management of BAV patients due to potential complications and the dynamic nature of the condition [7,12,22]. Regular medical evaluations, echocardiograms, and subsequent scans during follow-up enable the early detection of any alterations in valve structure, function, or aortic measurements [14,[23][24][25][26]. This early identification of complications allows for timely intervention, thwarting the progression of conditions like aortic stenosis or aneurysms.…”
Section: The Significance Of Regular Follow-up In Bicuspid Aortic Valvementioning
confidence: 99%
“…Consistent follow-up holds immense importance in the management of BAV patients due to potential complications and the dynamic nature of the condition [7,12,22]. Regular medical evaluations, echocardiograms, and subsequent scans during follow-up enable the early detection of any alterations in valve structure, function, or aortic measurements [14,[23][24][25][26]. This early identification of complications allows for timely intervention, thwarting the progression of conditions like aortic stenosis or aneurysms.…”
Section: The Significance Of Regular Follow-up In Bicuspid Aortic Valvementioning
confidence: 99%
“…Recent developments in imaging have suggested that the blood ow dynamics in the ascending aorta may be a major contributor to the BAV aortopathy [4,5] . Computational uid dynamics (CFD) is a useful tool that allows for the visualization of blood ow patterns [6,7] .…”
Section: Introductionmentioning
confidence: 99%